Rare earth ion doped fluoride scintillation crystal and preparation method thereof

By introducing Lu3+, Gd3+ and Sc3+ ions into the fluoride scintillation crystals, the core-shell structure is formed, which solves the problem of insufficient scintillation performance of existing scintillation crystals and achieves efficient X-ray imaging.

CN119736089AActive Publication Date: 2025-04-01CHINA JILIANG UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510244920.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-04
Publication Date
2025-04-01
Estimated Expiration
2045-03-04

AI Technical Summary

Technical Problem

Existing fluoride scintillation crystals have insufficient scintillation performance in X-ray imaging, making it difficult to meet the needs of low-dose lossless imaging.

Method used

Fluoride scintillation crystals doped with rare earth ions are used to introduce Lu3+ ions and Gd3+ ions into the core matrix and Sc3+ ions into the shell to form a core-shell structure, which improves the energy transfer efficiency and scintillation performance of rare earth activated ions.

Benefits of technology

It significantly improves the scintillation performance of rare earth activated ions, enhances luminous efficiency, reduces the chance of radiation-free relaxation, and is suitable for high-resolution low-dose X-ray imaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736089A_ABST
    Figure CN119736089A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of scintillation crystals, and discloses a rare earth ion doped fluoride scintillation crystal and a preparation method thereof, the chemical general formula of the scintillation crystal is NaLuF4: Gd / K / Xz at NaSc0. 2Lu0. 8F4, the core is NaLuF4: Gd / K / Xz, and the shell layer is NaSc < 0.2 > Lu0. 8F4; wherein X is one of Tb < 3 + >, Sm < 3 + >, Pr < 3 + > or Dy < 3 + > ions. In the process of preparing the core nanocrystals, excessive potassium sources are added, so that K < + > ions enter gaps of matrix crystal lattices to form defect state energy levels, and the energy transfer efficiency from secondary electrons to rare earth active ions is improved. According to the invention, the energy transfer efficiency of an ion excited state energy level can be improved, the scintillation performance of rare earth activated ions is enhanced together, the luminous efficiency is improved, and the non-radiative relaxation probability is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of scintillation crystals, and in particular to a fluoride scintillation crystal doped with rare earth ions and a preparation method thereof. Background Art

[0002] X-ray imaging technology based on traditional block scintillators usually requires high X-ray radiation doses to obtain high-quality images. For example, the effective radiation doses of a CT chest and coronary angiography examination are about 7 and 12 millisieverts, respectively, which may damage white blood cells in human blood, reduce the body's immune function, and lead to dangerous diseases. The development of new high-performance scintillator materials to achieve low-dose non-destructive X-ray imaging has important scientific research value.

[0003] Fluoride luminescent nanocrystals have been widely used in the field of biological imaging. The results show that fluoride nanocrystals have low toxicity and can be combined with biological tissues through surface modification. By controlling the size within a reasonable range, it is beneficial to the removal of nanocrystals, making them very suitable as matrix materials for activated ions. However, their scintillation performance still cannot meet the requirements of practical applications, and it is urgent to explore effective methods to significantly increase their light yield.

[0004] There are also some studies and applications related to scintillation crystals doped with rare earth ions and preparation methods in the prior art:

[0005] (1) For example, the invention patent with application number 201980002180.8, entitled "Garnet scintillator co-doped with monovalent ions", can also be applied to radiation detection fields such as medical imaging. The scintillator material [(RE1-xRE'x)1-y-zAyBz]3Al5O12 developed by the invention can be used to increase light output, improve energy resolution and accelerate attenuation components, and can be used in radiation detectors to detect gamma rays, X-rays, cosmic rays and / or particles with energy of 1keV or higher; or to prepare optical materials. Although the scintillator material of the research also contains rare earth ions such as Tb and / or Sc and / or Gd and / or Pr and / or Sm, the scintillator material is based on garnet doped with monovalent ions and belongs to the rare earth metal aluminum oxide garnet type scintillator material. The problem solved by the invention is that the garnet type scintillator materials (such as lutetium aluminum garnet, etc.) in the prior art have not yet realized their full potential when scintillation.

[0006] (2) Application No. 201711410854.7, entitled "Double-doped rare earth ion gadolinium gallium aluminum scintillating ceramic and its preparation method", which studies a Pr 3+ and Ce 3+Rare earth ion co-doping and gadolinium gallium aluminum scintillating ceramics that can achieve high light output and fast decay, and a method for preparing the above-mentioned gadolinium gallium aluminum scintillating ceramic material by chemical precipitation is studied. However, the gadolinium gallium aluminum scintillating ceramic material is based on Al3Ga2O12 and Pr 3+ and Ce 3+ It is made by co-doping with rare earth ions, but the luminous intensity is not enough for application in fields such as medical imaging.

[0007] (3) For example, the Chinese invention patent with application number 202010784126.8, entitled "A method and application of a polycrystalline sintered material and single crystal for preparing rare earth ion-doped fluoroaluminum calcium lithium ion scintillator crystals", mainly studies the growth of crystals under non-vacuum conditions, and can grow large-sized rare earth-doped fluoroaluminum calcium lithium ion crystals, which is conducive to promoting the mass production of rare earth ion-doped fluoroaluminum calcium lithium ion scintillator crystals.

[0008] (4) Application No. 201410249441.5, entitled A rare earth ion doped high-density fluorine oxyborogermanate scintillating glass and its preparation method, which effectively regulates the emission wavelength and attenuation time of this type of high-density scintillating glass by single doping (or co-doping) with different rare earth ion activators. However, it is mainly used to make optical fibers and to increase the density of the scintillating glass, reduce the cost of raw materials and the melting temperature of the glass.

[0009] (5) The Chinese invention patent application number is 200710028275.6, entitled "Trivalent cerium ion activated X-ray detection scintillation luminescent material and its preparation method". The material has high light yield and fast fluorescence decay, with the fluorescence decay time ranging from 10 to 25 nanoseconds. It will not deliquesce in the air and has good physical and chemical properties and scintillation luminescence properties. However, the material is based on PO3 and doped with trivalent cerium ions and the other two ions. Summary of the invention

[0010] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a fluoride scintillation crystal doped with rare earth ions and a preparation method thereof, which can improve the energy transfer efficiency of the ion excited state energy level, jointly enhance the scintillation performance of the rare earth activated ions, improve the luminous efficiency, reduce the probability of non-radiative relaxation, and prepare fluoride scintillation crystals doped with rare earth ions, which have good universality and provide new ideas for the development of high-performance scintillators.

[0011] The present invention is implemented by the following technical solution: a fluoride scintillating crystal doped with rare earth ions, the chemical composition formula of which is: NaLuF4:Gd / K / X z @NaSc 0.2 Lu 0.8 F4; core is NaLuF4:Gd / K / X z , the shell is NaSc 0.2Lu 0.8 F4; where X is Tb 3+ , Sm 3+ , Pr 3+ or Dy 3+ One of the ions; z is the molar content of X, 0.1≤z≤0.2.

[0012] Furthermore, the Lu in the core matrix is ​​a heavy metal element Lu 3+ Ions are used to increase the X-ray absorption coefficient and convert high-energy X-ray photons into low-energy secondary electrons.

[0013] Further, wherein Gd is Gd 3+ ions, in the process of preparing core nanocrystals, an excess of potassium source is added to make K + The ions enter the gaps of the matrix lattice to form defective energy levels, which play an energy bridging role and are used to improve the energy transfer efficiency from secondary electrons to rare earth activated ions; the defective energy levels are similar to those of Gd 3+ Ionic 6 P 7 / 2 The energy levels produce a synergistic effect and jointly enhance the scintillation performance of rare earth ions.

[0014] Further, the molar content z=0.15.

[0015] A method for preparing a fluoride scintillation crystal doped with rare earth ions, which is used to prepare the fluoride scintillation crystal doped with rare earth ions, comprises the following steps:

[0016] Step 1: adding 1-2 mmol of sodium acetate, 0.45-0.75 mmol of lutetium acetate, 2-3 mmol of potassium acetate, 0.05-0.15 mmol of acetate, and 0.1-0.2 mmol of gadolinium acetate to a mixed solution containing 6-8 ml of oleic acid and 8-12 ml of octadecene according to molar percentage, and keeping the mixture at 150° C. for 1 hour under the protection of nitrogen to obtain an anhydrous transparent solution;

[0017] Step 2: After the solution is cooled to room temperature naturally, add 8-15 ml of methanol solution containing 3-4 mmol of ammonium fluoride, and then keep warm at 60-90°C for half an hour;

[0018] Step 3: After the methanol solution is completely volatilized, the temperature is rapidly raised to 290-320°C, and kept at this temperature for 90-130 minutes, and then naturally cooled to room temperature;

[0019] Step 4: washing the obtained nanocrystals with a mixture of ethanol and cyclohexane to obtain NaLuF4:Gd / K / X core nanocrystals, which were stored in 4-6 ml of cyclohexane;

[0020] Step 5: adding 2 mmol of sodium acetate, 0.8 mmol of lutetium acetate and 0.2 mmol of scandium acetate according to molar percentage to a mixed solution containing 6-8 ml of oleic acid and 8-12 ml of octadecene, and keeping the mixture at 150° C. for 1 hour under the protection of nitrogen to obtain an anhydrous transparent solution;

[0021] Step 6: After the solution is naturally cooled to 70°C, the core nanocrystal solution obtained in step 4 is added to the reaction solution in step 5, and then heated at 80-100°C. o C keep warm for half an hour;

[0022] Step 7: After the solution is cooled to room temperature, add 8-15 ml of methanol solution containing 3-4 mmol of ammonium fluoride, and then o C keep warm for half an hour;

[0023] Step 8: After the methanol solution is completely volatilized, the temperature is rapidly raised to 290-320°C, and kept at this temperature for 90-130 minutes, and then naturally cooled to room temperature;

[0024] Step 9: Wash the obtained nanocrystals with a mixture of ethanol and cyclohexane, and dry them to obtain the final product NaLuF4:Gd / K / X@NaSc 0.2 Lu 0.8 F4 nano scintillating crystal.

[0025] Furthermore, the acetate in step 1 is terbium acetate, and the prepared nano-scintillating crystal is NaLuF4:Gd / K / Tb@NaSc 0.2 Lu 0.8 F4.

[0026] Furthermore, the acetate in step 1 is samarium acetate, and the prepared nano-scintillating crystal is NaLuF4:Gd / K / Sm@NaSc 0.2 Lu 0.8 F4.

[0027] Furthermore, the acetate in step 1 is praseodymium acetate, and the prepared nano-scintillating crystal is NaLuF4:Gd / K / Pr@NaSc 0.2 Lu 0.8 F4.

[0028] Furthermore, the acetate in step 1 is dysprosium acetate, and the prepared nano-scintillating crystal is NaLuF4:Gd / K / Dy@NaSc 0.2 Lu 0.8 F4.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] 1. A fluoride scintillating crystal doped with rare earth ions according to the present invention contains the heavy metal element Lu 3+ The ions can effectively convert high-energy X-rays into low-energy secondary electrons; excess K ions enter the gaps in the matrix lattice, generating defects and forming defect state energy levels, which play an energy bridging role and improve the energy transfer efficiency from secondary electrons to the excited state energy levels of rare earth activated ions.

[0031] 2. A fluoride scintillating crystal doped with rare earth ions of the present invention is similar to the defect state energy level, Gd 3+ Ionic 6 P 7 / 2 The energy level can also increase the secondary electrons to rare earth activated ions Tb 3+ , Sm 3+ , Pr 3+ or Dy 3+ The energy transfer efficiency, defect state energy level and Gd 3+ Ionic 6 P 7 / 2 The energy levels produce a synergistic effect and can jointly enhance the scintillation performance of rare earth activated ions.

[0032] 3. A rare earth ion-doped fluoride scintillating crystal of the present invention, NaSc 0.2 Lu 0.8 The F4 shell can passivate the surface of the nanocrystal, reduce the probability of non-radiative relaxation of rare earth activated ions, improve the luminescence efficiency, and introduce a small amount of Sc into the shell. 3+ , which can tailor the interface phonon state density and further reduce the probability of non-radiative relaxation.

[0033] 4. The preparation method of the rare earth ion-doped fluoride scintillating crystal of the present invention is simple, and the obtained product has high yield, good dispersibility and uniform shape, which lays a solid experimental technical foundation for the research and development of high-resolution and low-dose X-ray imaging technology and provides a universal method for the development of high-performance scintillator materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 : NaLuF4:Gd / K / Tb@NaSc in Example 1 0.2 Lu 0.8 X-ray diffraction pattern of F4 nano-scintillating material;

[0035] Figure 2 : NaLuF4:Gd / K / Tb@NaSc in Example 1 0.2 Lu 0.8 Transmission electron microscopy image of F4 nano-scintillating material;

[0036] Figure 3 : NaLuF4:Gd / K / Tb@NaSc in Example 10.2 Lu 0.8 Scintillation spectrum of F4 nano-scintillating material under X-ray excitation;

[0037] Figure 4 : NaLuF4:Gd / K / Tb@NaSc in Example 1 0.2 Lu 0.8 The luminescence intensity of F4 nano-scintillating material under X-ray excitation is similar to that of Gd 3+ The relationship curve of ion concentration;

[0038] Figure 5 : NaLuF4:Gd / K / Sm@NaSc in Example 2 0.2 Lu 0.8 Scintillation spectrum of F4 nano-scintillating material under X-ray excitation;

[0039] Figure 6 : NaLuF4:Gd / K / Pr@NaSc in Example 3 0.2 Lu 0.8 Scintillation spectrum of F4 nano-scintillating material under X-ray excitation;

[0040] Figure 7 : NaLuF4:Gd / K / Dy@NaSc in Example 4 0.2 Lu 0.8 Scintillation spectrum of F4 nano-scintillating material under X-ray excitation;

[0041] Figure 8 : The scintillation luminescence integrated intensity variation curves of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3;

[0042] Fig. 9 : Comparison diagram of the scintillation luminescence integrated intensity of Example 2 and Comparative Example 4;

[0043] Fig.10 : Comparison diagram of the scintillation luminescence integrated intensity of Example 3 and Comparative Example 5;

[0044] Fig.11 : The scintillation luminescence integrated intensity variation curve diagram of Example 4 and Comparative Example 6;

[0045] Fig.12 : Comparison of the scintillation luminescence integrated intensity of Example 1 and commercial CsI (Tl) scintillator. DETAILED DESCRIPTION

[0046] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the following embodiments and features in the embodiments can be combined with each other without conflict.

[0047] Example 1

[0048] A fluoride scintillating crystal doped with rare earth ions has a general chemical composition formula of:

[0049] NaLuF4:Gd / K / X z @NaSc 0.2 Lu 0.8 F4;

[0050] Its structure is a core-shell two-layer structure, the core is NaLuF4:Gd / K / X z , the shell is NaSc 0.2 Lu 0.8 F4;

[0051] Where X is Tb 3+ , Sm 3+ , Pr 3+ or Dy 3+ One of the ions; z is the molar content of X, z=0.2.

[0052] Where NaLuF4:Gd / K / X z The Lu in the nuclear matrix is ​​the heavy metal element Lu 3+ Ions are used to increase the X-ray absorption coefficient and convert high-energy X-ray photons into low-energy secondary electrons. 3+ ions, in the process of preparing core nanocrystals, an excess of potassium source is added to make K + The ions enter the gaps of the matrix lattice to form defective energy levels, which play an energy bridging role and are used to improve the energy transfer efficiency from secondary electrons to rare earth activated ions; the defective energy levels are similar to those of Gd 3+ Ionic 6 P 7 / 2 The energy levels produce a synergistic effect, which jointly enhances the scintillation performance of rare earth ions. 0.2 Lu 0.8 The shell of F4 can not only passivate the surface of nanocrystals, but also tailor the interface phonon state density, greatly reducing the probability of non-radiative relaxation, thereby greatly improving the scintillation luminescence efficiency.

[0053] A method for preparing a fluoride scintillating crystal doped with rare earth ions, in this embodiment, NaLuF4:Gd / K / Tb 0.2 @NaSc 0.2 Lu 0.8 F4 is taken as an example, and its preparation method comprises the following steps:

[0054] Step 1: adding 2 mmol of sodium acetate, 0.7 mmol of lutetium acetate, 3 mmol of potassium acetate, 0.15 mmol of terbium acetate and 0.15 mmol of gadolinium acetate to a mixed solution containing 8 ml of oleic acid and 10 ml of octadecene according to molar percentage, and keeping the mixture at 150° C. for 1 hour under the protection of nitrogen to obtain an anhydrous transparent solution;

[0055] Step 2: After the solution is cooled to room temperature naturally, add 10 ml of methanol solution containing 3 mmol of ammonium fluoride, and then keep it at 80°C for half an hour;

[0056] Step 3: After all the methanol solution has evaporated, the temperature is rapidly raised to 300°C, and kept at this temperature for 100 minutes, and then naturally cooled to room temperature;

[0057] Step 4: Wash the obtained nanocrystals with a mixture of ethanol and cyclohexane to obtain NaLuF4:Gd / K / Tb 0.2 Core nanocrystals, stored in 5 mL of cyclohexane;

[0058] Step 5: adding 2 mmol of sodium acetate, 0.8 mmol of lutetium acetate and 0.2 mmol of scandium acetate according to molar percentage to a mixed solution containing 6 ml of oleic acid and 8 ml of octadecene, and keeping the mixture at 150° C. for 1 hour under the protection of nitrogen to obtain an anhydrous transparent solution;

[0059] Step 6: After the solution is naturally cooled to 70°C, the core nanocrystal solution obtained in step 4 is added to the reaction solution in step 5, and then heated at 100 o C keep warm for half an hour;

[0060] Step 7: After the solution is cooled to room temperature, add 8 ml of methanol solution containing 3 mmol of ammonium fluoride, and then o C keep warm for half an hour;

[0061] Step 8: After the methanol solution is completely volatilized, the temperature is quickly raised to 300°C, and kept at this temperature for 90 minutes, and then naturally cooled to room temperature;

[0062] Step 9: Wash the obtained nanocrystals with a mixture of ethanol and cyclohexane, and dry them to obtain the final product NaLuF4:Gd / K / Tb 0.2 @NaSc 0.2 Lu 0.8F4 nano scintillating crystal.

[0063] Reference Figure 1 As shown, for NaLuF4:Gd / K / Tb 0.2 @NaSc 0.2 Lu 0.8 The powder of F4 nano-scintillator crystal was subjected to X-ray diffraction analysis, and the powder X-ray diffraction analysis showed that the product was a pure hexagonal phase.

[0064] Reference Figure 2 As shown, transmission electron microscopy analysis showed that the average crystallite size of the product was 45 nm.

[0065] Reference Figure 3 As shown, under X-ray excitation conditions, the nano-scintillating crystal exhibits Tb 3+ The characteristic transition spectral lines, including the 4f-4f transition, show maximum intensity at a wavelength of about 550 nanometers, with a maximum intensity of 120,000.

[0066] The product has a rich energy level structure, and the matching degree between the secondary electron and the excited state energy level has a significant influence on the luminescence performance. Figure 4 As shown, with Gd 3+ As the ion doping concentration increases from 0 to 15% (molar percentage), the luminescence intensity increases by about 5 times, mainly due to the increase in the secondary electrons to Tb 3+ ion energy transfer efficiency, but Gd 3+ When the ion doping concentration exceeds 15%, its luminescence intensity begins to weaken.

[0067] Example 2

[0068] A fluoride scintillating crystal doped with rare earth ions has a general chemical composition formula of:

[0069] NaLuF4:Gd / K / Sm@NaSc 0.2 Lu 0.8 F4;

[0070] The preparation method is the same as that of NaLuF4:Gd / K / Tb in Example 1. 0.2 @NaSc 0.2 Lu 0.8 The difference of F4 is that the terbium acetate in step 1 is replaced by samarium acetate, and the other steps remain unchanged.

[0071] Reference Figure 5 As shown, under X-ray excitation conditions, NaLuF4:Gd / K / Sm@NaSc 0.2 Lu 0.8 F4 shows maximum intensity at a wavelength of around 600 nanometers, with a maximum intensity of 18,000.

[0072] Example 3

[0073] A fluoride scintillating crystal doped with rare earth ions has a general chemical composition formula of:

[0074] NaLuF4:Gd / K / Pr@NaSc 0.2 Lu 0.8 F4;

[0075] The preparation method is the same as that of NaLuF4:Gd / K / Tb in Example 1. 0.2 @NaSc 0.2 Lu 0.8 The difference of F4 is that terbium acetate in step 1 is replaced by praseodymium acetate, and the other steps remain unchanged.

[0076] Reference Figure 6 As shown, under X-ray excitation conditions, NaLuF4:Gd / K / Pr@NaSc 0.2 Lu 0.8 F4 shows maximum intensity at around 460 nanometers wavelength, with a maximum intensity of 16,000.

[0077] Example 4

[0078] A fluoride scintillating crystal doped with rare earth ions has a general chemical composition formula of:

[0079] NaLuF4:Gd / K / Dy@NaSc 0.2 Lu 0.8 F4;

[0080] The preparation method is the same as that of NaLuF4:Gd / K / Tb in Example 1. 0.2 @NaSc 0.2 Lu 0.8 The difference of F4 is that the terbium acetate in step 1 is replaced by dysprosium acetate, and the other steps remain unchanged.

[0081] Reference Figure 7 As shown, under X-ray excitation conditions, NaLuF4:Gd / K / Dy@NaSc 0.2 Lu 0.8 F4 shows maximum intensity at around 580 nanometers wavelength, with a maximum intensity of 45,000.

[0082] The four fluoride scintillation crystals prepared by the above method can produce very strong scintillation luminescence under X-ray excitation. 3+ , Sm 3+ , Pr 3+ With Dy 3+ The characteristic spectral lines of the four ions can also be detected.

[0083] In order to better illustrate the advantages of the structural system of the present invention, the present invention also sets three comparative examples for Example 1.

[0084] Comparative Example 1

[0085] The difference between the preparation method of comparative example 1 and the preparation method of fluoride scintillation crystal in Example 1 is that the preparation method of comparative example 1 only includes steps 1 to 4 in Example 1, and there is no potassium acetate raw material in step 4, and the other steps remain unchanged.

[0086] Comparative Example 1 prepared NaLuF4:Gd / Tb nano-scintillating material.

[0087] Comparative Example 2

[0088] The difference between the preparation method of comparative example 2 and the preparation method of the fluoride scintillation crystal in Example 1 is that the preparation method of comparative example 2 only includes steps 1 to 4 in Example 1, and the other steps remain unchanged.

[0089] Comparative Example 2 prepared NaLuF4:Gd / K / Tb nano-scintillating material.

[0090] Comparative Example 3

[0091] The difference between the preparation method of Comparative Example 3 and the preparation method of the fluoride scintillation crystal in Example 1 is that the preparation method of Comparative Example 3 does not contain scandium acetate in step 5, and the other steps remain unchanged.

[0092] Comparative Example 3 prepared NaLuF4:Gd / K / Tb@NaLuF4 nano-scintillating material.

[0093] Reference Figure 8 As shown, under X-ray excitation conditions, the overall integrated intensity trends of the three comparative examples and Example 1 are: Example 1>Comparative Example 3>Comparative Example 2>Comparative Example 1. This indicates that the excess K in the raw material + It can form defect energy levels in the matrix lattice, improve the electron filling efficiency of the excited state energy level of rare earth ions, and introduce Sc into the shell 3+ Ions can reduce the interface phonon state density and the probability of non-radiative relaxation, thereby improving the scintillation performance.

[0094] In order to further illustrate the advantages and universality of the structural system of the present invention, the present invention also sets a comparative example for each of Example 2, Example 3 and Example 4.

[0095] Comparative Example 4

[0096] The difference between the preparation method of Comparative Example 4 and the preparation method of the fluoride scintillation crystal in Example 2 is that Comparative Example 4 only includes steps 1 to 4 in Example 2, and there is no potassium acetate raw material in step 1, and the other steps remain unchanged.

[0097] Comparative Example 4 prepared NaLuF4:Gd / Sm nano-scintillating material.

[0098] Reference Fig. 9 As shown, under the X-ray excitation condition, its overall integrated intensity is still significantly lower than that of Example 2, and the overall integrated intensity of Example 2 is nearly 6 times that of Comparative Example 4, which shows that the NaLuF4:Gd / K / Sm@NaSc designed in Example 2 0.2 Lu 0.8 The F4 structure can significantly increase the Sm 3+ Scintillation properties of ions.

[0099] Comparative Example 5

[0100] The difference between the preparation method of Comparative Example 5 and the preparation method of the fluoride scintillation crystal in Example 3 is that Comparative Example 5 only includes steps 1 to 4 in Example 3, and there is no potassium acetate raw material in step 1, and the other steps remain unchanged.

[0101] Comparative Example 5 prepared NaLuF4:Gd / Pr nano-scintillating material.

[0102] Reference Fig.10 As shown, under X-ray excitation conditions, its overall integrated intensity is still significantly lower than that of Example 3, and the overall integrated intensity of Example 3 is nearly 10 times that of Comparative Example 5, which shows that the NaLuF4:Gd / K / Pr@NaSc designed in Example 3 0.2 Lu 0.8 The F4 structure can significantly increase the Pr 3+ Scintillation properties of ions.

[0103] Comparative Example 6

[0104] The difference between the preparation method of Comparative Example 6 and the preparation method of the fluoride scintillation crystal in Example 4 is that Comparative Example 6 only includes steps 1 to 4 in Example 3, and there is no potassium acetate raw material in step 1, and the other steps remain unchanged.

[0105] Comparative Example 6 prepared NaLuF4:Gd / Dy nano-scintillating material.

[0106] Reference Fig.11 As shown, under the X-ray excitation condition, its overall integrated intensity is still significantly lower than that of Example 4, and the overall integrated intensity of Example 4 is nearly 8 times that of Comparative Example 6, which indicates that the NaLuF4:Gd / K / Dy@NaSc designed in Example 4 0.2 Lu 0.8 The F4 structure can significantly increase the Dy 3+ Scintillation properties of ions.

[0107] In order to further verify that the structural system of the present invention has good scintillation performance, NaLuF4:Gd / K / Tb@NaSc 0.2 Lu 0.8 The performance of F4 was compared with that of commercial CsI(Tl) scintillators. Fig.12 As shown, NaLuF4:Gd / K / Tb@NaSc 0.2 Lu 0.8 The scintillation intensity of F4 is 3.2 times that of CsI(Tl) scintillator.

[0108] The preparation method of the present invention and the four fluoride scintillation crystals prepared therefrom are special in that:

[0109] (1) Heavy metal element Lu 3+ Ions can efficiently convert high-energy X-rays into low-energy secondary electrons;

[0110] (2) Excess K + The ions enter the gaps in the matrix lattice to form defective energy levels, which play an energy bridging role and improve the energy transfer efficiency from secondary electrons to rare earth activation ions;

[0111] (3) Gd 3+ Ionic 6 P 7 / 2 The energy level can improve the energy transfer efficiency from secondary electrons to rare earth activated ions. The defect state energy level is similar to that of Gd 3+ Ionic 6 P 7 / 2 The energy levels produce a synergistic effect, which together greatly enhances the scintillation performance of rare earth activated ions;

[0112] (4) NaSc 0.2 Lu 0.8 The F4 shell can passivate the surface of the nanocrystal, reduce the probability of radiationless relaxation of rare earth activated ions, and introduce a small amount of Sc into the shell. 3+ , which can tailor the interface phonon state density and further reduce the probability of non-radiative relaxation, thereby greatly improving the scintillation luminescence efficiency.

[0113] (5) The preparation method is simple, and the obtained product has high yield, good dispersibility and uniform shape.

[0114] The present invention provides a method for preparing a high-performance scintillator material, which lays a solid experimental technical foundation for the research and development of high-resolution, low-dose X-ray imaging technology. The prepared high-performance scintillator material is expected to be applied in the imaging field.

[0115] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A fluoride scintillating crystal doped with rare earth ions, characterized in that: The general chemical formula is: NaLuF4:Gd / K / X z @NaSc 0.2 Lu 0.8 F4; The core is NaLuF4:Gd / K / X z , the shell is NaSc 0.2 Lu 0.8 F4; Where X is Tb 3+ , Sm 3+ , Pr 3+ or Dy 3+ One of the ions; z is the molar content of X, 0.1≤z≤0.

2.

2. The rare earth ion-doped fluoride scintillating crystal according to claim 1, characterized in that: The Lu in the nuclear matrix is ​​the heavy metal element Lu 3+ Ions are used to increase the X-ray absorption coefficient and convert high-energy X-ray photons into low-energy secondary electrons.

3. The rare earth ion-doped fluoride scintillating crystal according to claim 2, characterized in that: Where Gd is Gd 3+ ion; During the preparation of core nanocrystals, an excess of potassium source is added to make K + The ions enter the gaps in the matrix lattice to form defective energy levels, which play an energy bridging role and are used to improve the energy transfer efficiency from secondary electrons to rare earth activation ions; Defect state energy level and Gd 3+ Ionic 6 P 7 / 2 The energy levels produce a synergistic effect and jointly enhance the scintillation performance of rare earth ions.

4. The rare earth ion-doped fluoride scintillating crystal according to claim 3, characterized in that: Molar content z=0.

15.

5. The method for preparing the rare earth ion-doped fluoride scintillating crystal according to claim 4, characterized in that: The steps include: Step 1: adding 1-2 mmol of sodium acetate, 0.45-0.75 mmol of lutetium acetate, 2-3 mmol of potassium acetate, 0.05-0.15 mmol of acetate, and 0.1-0.2 mmol of gadolinium acetate to a mixed solution containing 6-8 ml of oleic acid and 8-12 ml of octadecene according to molar percentage, and keeping the mixture at 150° C. for 1 hour under the protection of nitrogen to obtain an anhydrous transparent solution; Step 2: After the solution is cooled to room temperature naturally, add 8-15 ml of methanol solution containing 3-4 mmol of ammonium fluoride, and then keep warm at 60-90°C for half an hour; Step 3: After the methanol solution is completely volatilized, the temperature is rapidly raised to 290-320°C, and kept at this temperature for 90-130 minutes, and then naturally cooled to room temperature; Step 4: washing the obtained nanocrystals with a mixture of ethanol and cyclohexane to obtain NaLuF4:Gd / K / X core nanocrystals, which were stored in 4-6 ml of cyclohexane; Step 5: adding 2 mmol of sodium acetate, 0.8 mmol of lutetium acetate and 0.2 mmol of scandium acetate according to molar percentage to a mixed solution containing 6-8 ml of oleic acid and 8-12 ml of octadecene, and keeping the mixture at 150° C. for 1 hour under the protection of nitrogen to obtain an anhydrous transparent solution; Step 6: After the solution is naturally cooled to 70°C, the core nanocrystal solution obtained in step 4 is added to the reaction solution in step 5, and then heated at 80-100°C. o C keep warm for half an hour; Step 7: After the solution is cooled to room temperature, add 8-15 ml of methanol solution containing 3-4 mmol of ammonium fluoride, and then o C keep warm for half an hour; Step 8: After the methanol solution is completely volatilized, the temperature is rapidly raised to 290-320°C, and kept at this temperature for 90-130 minutes, and then naturally cooled to room temperature; Step 9: Wash the obtained nanocrystals with a mixture of ethanol and cyclohexane, and dry them to obtain the final product NaLuF4:Gd / K / X@NaSc 0.2 Lu 0.8 F4 nano scintillating crystal.

6. The method for preparing the rare earth ion-doped fluoride scintillating crystal according to claim 5, characterized in that: The acetate in step 1 is terbium acetate, and the prepared nano-scintillating crystal is NaLuF4:Gd / K / Tb@NaSc 0.2 Lu 0.8 F4.

7. The method for preparing the rare earth ion-doped fluoride scintillating crystal according to claim 5, characterized in that: The acetate in step 1 is samarium acetate, and the prepared nano-scintillating crystal is NaLuF4:Gd / K / Sm@NaSc 0.2 Lu 0.8 F4.

8. The method for preparing the rare earth ion-doped fluoride scintillating crystal according to claim 5, characterized in that: The acetate in step 1 is praseodymium acetate, and the prepared nano-scintillating crystal is NaLuF4:Gd / K / Pr@NaSc 0.2 Lu 0.8 F4.

9. The method for preparing the rare earth ion-doped fluoride scintillating crystal according to claim 5, characterized in that: The acetate in step 1 is dysprosium acetate, and the prepared nano-scintillating crystal is NaLuF4:Gd / K / Dy@NaSc 0.2 Lu 0.8 F4.

Citation Information

Patent Citations

  • Method for increasing doping concentration of Tm&lt;3+&gt; in up-conversion luminescence nanocrystals

    CN106566527A

  • Rare earth doped sodium lutetium fluoride up-conversion luminescence nano-material and preparation method thereof

    CN107163945A

  • High-performance wide-band scintillator material

    CN114164001A

  • Red-light fluoride nanocrystalline scintillator and preparation method thereof

    CN114606002A

  • High-performance single rare earth doped fluoride, flexible scintillation screen and application

    CN119371969A